The Implementation of Mobile Application for Queue Management and Customer Service at Babe Barbershop Using Agile Method - Musa Alhadi Pulungan; Devi Sartika; Ahmad Asyhari (Jurnal Media Computer Science, 2026)
Babe Barbershop faced manual queuing problems that affected schedule irregularities and customer comfort. This research aims to design and implement a more efficient and structured mobile application for queue management and customer service. Development was carried out at Babe Barbershop (Bengkulu) from February to June 2025 using Agile method with iterative stages from planning to launch, in order to easily adapt to changing needs. The application was developed with Vue.js and Firebase stack; key features include registration/login, service booking with barber and time slot selection, attendance confirmation, walk-in input, barber dashboard, and a public queue page for transparency. Black-box testing showed that all functions worked well according to the scenario: bookings were saved and had a BOOKED status, cancellations updated the status, “Already Present” changed the status and barber queue, and application navigation was smooth without errors. These results confirm that the application supports operational efficiency, reduces waiting times, and improves the service experience at Babe Barbershop..